PENGARUH PENGHASILAN, LITERASI PAJAK, PEMANFAATAN APLIKASI PAJAK, DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK: Studi Pada Wajib Pajak Wilayah Kantor Pelayanan Pajak Pratama Pondok Aren - Rona Tumiur Mauli Carolin , Simorangkir (JMD : Jurnal Riset Manajemen & Bisnis Dewantara, 2023)
This research aims to analyze the influence of income, tax literacy, use of tax applications, taxpayer awareness on MSME taxpayer compliance. This study uses a quantitative approach. The population in this research is MSME Taxpayers in the KPP Pratama Pondok Aren Area. The sample in this study was 100 respondents. The data used is primary data taken from questionnaires distributed to respondents. Data analysis used in this research used SmartPLS Version 3.0 software. The results of this research show that the influence of income, tax literacy, use of tax applications and taxpayer awareness has a positive and significant influence on MSME taxpayer compliance at KPP Pratama Pondok Aren.